Complete chloroplast genome of a coastal herb, Linaria japonica Miquel 1865 (Plantaginaceae) - Iseon Kim; Yongsung Kim; Changkyun Kim (Mitochondrial DNA. Part B. Resources)
Linaria japonica Miquel 1865 (Plantaginaceae) is a perennial herb found in coastal areas of north-east China, Japan, Korea, and the Far East Russia. Here, we report the complete chloroplast genome of L. japonica and determine its systematic position in 11 tribes of Plantaginaceae. The size of complete chloroplast genome was 150,660 bp, consisting of a pair of inverted repeats (25,647 bp each) separated by a large single-copy region (81,766 bp) and a small single-copy region (17,600 bp). Our phylogenomic analyses using 78 protein-coding genes show that Linaria belongs to the tribe Antirrhineae. Within Linaria, L. japonica is sister to L. buriatica Turcz.